Introduction to special issue: linguistic racism - Dovchin, Sender (2020)
Papers in this Special Issue, “Linguistic Racism”, focus on the phenomenon of linguistic racism–the ideologies and practices that are utilised to conform, normalise and reformulate an unequal and uneven linguistic power between language users (Skutnabb-Kangas 2015)–directed at culturally and linguistically different (CaLD) or Indigenous backgrounds around the globe. The authors provide multiple ethnographic studies to understand what it means to speak as a racialised subject in the highly diverse societies of the twenty-first century, examining the manners in which one’s fundamental human rights are violated, and how one is deprived of both socio-economic and socio-cultural opportunities as a result of their use of language. All of the articles acknowledge the multiple, complex layers of cause and effect that further entrenches linguistic racism into particular social, cultural, ethnic, national and educational contexts that (re)shape the minoritised bilingual speakers’ linguistic practices. The Special Issue addresses the effects of critical approaches to current bilingualism theories that break new ground by disclosing the reality that it is not always applicable to commend bilingual diversity without fully acknowledging ongoing, often profoundly entrenched, local constraints.